A SCIENTIFIC ANALYSIS OF THE HERITAGE OF ABU HANIFAH REGARDING THE SCIENCE OF ʻAQAʼID - Sulaymanov Dilmurod Makhammatjanovich (Scholars Digest Publishing, 2023)
In this article, opinions are given about the merits of Abū Ḥanīfah in spreading the correct interpretation of the doctrine and creed of Māturīdiyyah among the people, his works on creed and jurisprudence, and it is said that the most mentioned works are proved by scientific grounds.
Keywords: Abū Ḥanīfah, ʿaqīdah, Māturīdiyyah, kalām, fiqh, Ibn al-Nadīm,